Mini-FLOTAC, an Innovative Direct Diagnostic Technique for Intestinal Parasitic Infections: Experience from the Field - Barda, Beatrice Divina; Rinaldi, Laura; Ianniello, Davide; Zepherine, Henry; Salvo, Fulvio; Sadutshang, Tsetan; Cringoli, Giuseppe; Clementi, Massimo; Albonico, Marco (PLoS neglected tropical diseases, 2013)
Soil-transmitted helminths and intestinal protozoa infection are widespread in developing countries, yet an accurate diagnosis is rarely performed. The aim of this study was to evaluate the recently developed mini-FLOTAC method and to compare with currently more widely used techniques for the diagnosis of intestinal parasitic infections in different settings. The study was carried out in Dharamsala, Himachal Pradesh, India, and in Bukumbi, Tanzania. A total of 180 pupils from two primary schools had their stool analyzed (n = 80 in Dharamsala and n = 100 in Bukumbi) for intestinal parasitic infections with three diagnostic methods: direct fecal smear, formol-ether concentration method (FECM) and mini-FLOTAC. Overall, 72% of the pupils were positive for any intestinal parasitic infection, 24% carried dual infections and 11% three infections or more. The most frequently encountered intestinal parasites were Entamoeba coli, Entamoeba histolytica/dispar, Giardia intestinalis, hookworm, (and Schistosoma mansoni, in Tanzania). Statistically significant differences were found in the detection of parasitic infections among the three methods: mini-FLOTAC was the most sensitive method for helminth infections (90% mini-FLOTAC, 60% FECM, and 30% direct fecal smear), whereas FECM was most sensitive for intestinal protozoa infections (88% FECM, 70% direct fecal smear, and 68% mini-FLOTAC). We present the first experiences with the mini-FLOTAC for the diagnosis of intestinal helminths and protozoa. Our results suggest that it is a valid, sensitive and potentially low-cost alternative technique that could be used in resource-limited settings--particularly for helminth diagnosis.